Respuesta :

Answer:

X=6x+30/x

Step-by-step explanation:

just simplify

Answer:

x = 3 ± √(39)

Step-by-step explanation:

x            6

-----   = -------

(x+5)      x

We can solve using cross products

x * x = 6(x+5)

x^2 = 6x+30

Subtract 6x from each side

x^2 -6x= 6x+30-6x

x^2 -6x= 30

Subtract 30 from each side

x^2 -6x -30 = 30-30

x^2 -6x -30 =0

Using the quadratic formula

x = -b ± √(b^2 -4ac)

     -------------------------

                2a

where  a=1  b = -6  and c = -30

x = -(-6) ± √((-6)^2 -4(1)(-30))

     -------------------------

                2(1)

x = 6 ± √(36 +120)

     -------------------------

                2

x = 6 ± √(156)

     -------------------------

               2

x = 6 ± √(4*39)

     -------------------------

                2

x = 6 ± 2√(39)

     -------------------------

                2

x = 3 ± √(39)